'Going to school to become good people': Examining aspirations to respectability and goodness among schoolchildren in urban Ethiopia. (August 2016) - Marshall, Lydia
This article examines the factors leading children in Hawassa, Ethiopia, to want to go to school in order 'to become good people'. Drawing on a critical realist understanding of human agency, it argues that children's motivations for going to school rested both on their 'ultimate', moral concerns and 'ideas of the good' and on external generative mechanisms that led them to identify participation in formal education as the key to becoming a 'good' person.